Identification and Characterization of the cps Locus of Streptococcus suis Serotype 2: the Capsule Protects against Phagocytosis and Is an Important Virulence Factor - Smith, Hilde E. (American Society for Microbiology, 1999)
To study the role of the capsule of Streptococcus suis serotype 2 in virulence, we generated two isogenic mutants disturbed in capsule production. For that purpose, we first cloned and characterized a major part of the capsular polysaccharide biosynthesis (cps) locus of S. suis serotype 2. Based on the established sequence, 14 open reading frames (ORFs), designated Orf2Z, Orf2Y, Orf2X, and Cps2A to Cps2K, were identified. Twelve ORFs belonged to a single transcriptional unit. The gene products of 11 of these ORFs showed similarity to proteins involved in polysaccharide biosynthesis of other gram-positive microorganisms. Nonencapsulated isogenic mutants were generated in the cps2B and cps2EF genes by insertional mutagenesis. In contrast to the wild-type S. suis serotype 2 strain, the nonencapsulated strains were highly sensitive to ingestion by porcine alveolar lung macrophages in vitro. More importantly, the nonencapsulated mutant strains were completely avirulent in young germfree pigs after intranasal inoculation. These observations indicate that the capsule of S. suis serotype 2 plays an essential role in the pathogenesis of S. suis serotype 2 infections.